2017
DOI: 10.26530/oapen_630630
|View full text |Cite
|
Sign up to set email alerts
|

Yyteistä uuteen alkuun : toimittajien kertomuksia mediatyön murroksesta

Abstract: Kannen kuva Anssi MännistöGraafinen suunnittelu ja taitto Sirpa Randell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…1. Previous research on mobile news consumption and production in Finland can be found in Ahlroth (2012), Harju, Männistö, and Heinonen (2011), Koponen and Väätäjä (2009), and Pekonen (2012). Importantly, these studies have not focused on mobile UDC, so our study is the first to offer such insights.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…1. Previous research on mobile news consumption and production in Finland can be found in Ahlroth (2012), Harju, Männistö, and Heinonen (2011), Koponen and Väätäjä (2009), and Pekonen (2012). Importantly, these studies have not focused on mobile UDC, so our study is the first to offer such insights.…”
Section: Acknowledgementsmentioning
confidence: 99%